Profil “Kontemporer” Musik Kelahiran Minang - Mahdi Bahar (Mudra Jurnal Seni Budaya, 2007)
one of musical entities in West Sumatera is the Minangkabau cultural music. The existence of the music has changed significantly since the second half of twentieth century, as an intergral change of Indonesian music in general. Following the situation I see the emergence of academic discussions on the music in a member of forums in this republic. In the discussion, many terms are adopted from foreign languages, especially English, such as “contemporary”. Various meanings given to “contemporary” are used to define the phenomena of changes in music in the countri. One of a newly-created music as a phenomenon of change in the Minangkabau cultural context is “Kawin Silang” composition. The composition in this article is discussed in the contemporary perspective.